Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.2176/nmc.47.495
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Perioperative Cardiac Complications After Lumbar Fusion Surgery

Abstract: Cardiac complication is a leading cause of death in the perioperative period after non-cardiac surgery. The present study retrospectively investigated perioperative cardiac complications after spinal fusion surgery in 901 consecutive adult patients who underwent fusion surgery in the lumbar spine from January 2005 to December 2006. Cardiac complications developed in seven patients (0.8%), four males and three females aged 62 to 75 years (mean 66.6 years), in the perioperative period (myocardial infarction in 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…For example, while it is intuitive that a larger surgical procedure with greater anesthetic time and blood loss would be associated with greater medical risk to the patient, this finding is inconsistently reported. Some studies have reported that arthrodesis increases medical complications 1,5 as compared to non-fusion surgeries and other studies have suggested there is no correlation 2,7,12 . Similarly, the associations of age and medical co-morbidity to post operative medical complication after spine surgery have been inconsistently reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, while it is intuitive that a larger surgical procedure with greater anesthetic time and blood loss would be associated with greater medical risk to the patient, this finding is inconsistently reported. Some studies have reported that arthrodesis increases medical complications 1,5 as compared to non-fusion surgeries and other studies have suggested there is no correlation 2,7,12 . Similarly, the associations of age and medical co-morbidity to post operative medical complication after spine surgery have been inconsistently reported.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the associations of age and medical co-morbidity to post operative medical complication after spine surgery have been inconsistently reported. 1,2,4,7,11,12 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the results of the present study may seem intuitive, the influence of these risk factors has been questioned in the literature 2,7,11…”
Section: Discussionmentioning
confidence: 64%
“…Cardiac complications are a leading cause of death after non-cardiac surgery 4,5,10. Lee et al reported a 0.8% incidence of cardiac complications after lumbar fusion in retrospective review of 901 patients,11 but identification of statistically significant risk factors was limited by the study methodology.…”
Section: Study Rationalementioning
confidence: 99%